Classification of caesarean section based on Robson ten group classification system in our hospital - Sharma, Ari; Singh, Dipika; Verma, Sarika; Sharma, Sanjog (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Recent data indicate that one in five women undergo caesarean section (CS). In the last decade, there has been a dramatic increase in the caesarean section rate worldwide, which now exceeds 30% in some regions. Thus, the increasing rate of caesarean section became a matter of international public health concern. Our study aimed to classify the CS-based on Robson ten group classification system (RTGCS) criteria which will subsequently enable us to standardise the indication of CS and establish protocols to reduce the number of CS in our set up. Method: A retrospective study was conducted in ESI Hospital, New Delhi wherein Robson TGCS was used to classify CS for 15 months (January 2019 to April 2020). Results: Overall CS rate in our hospital over the specified period was 34.5%. All women with one or more previous cesareans (group V) had the maximum number of cesareans, 37%, followed by nulliparous, single, cephalic, term pregnancy (induced) i.e group II, 22.1% and nulliparous women more than 37 weeks in spontaneous labour (group I), 9.5%. Conclusions: RTGCS is easy to comprehend and reproduce. All deliveries and cesareans should be universally categorized by the Robsons TGCS. An attempt should be made to evaluate the group contributing most to the CS rate and interventions should be made accordingly.